IMPACT OF STRATEGIC LEADERSHIP ON ENHANCING STRATEGIC HUMAN RESOURCE MANAGEMENT PRACTICES IN VOLLEYBALL FEDERATIONS IN IRAQ - Tahseen Allawi Adil; Munadhil Adil Kasim (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2026)
The present research seeks to study the impact of strategic leadership in its various dimensions, namely: defining the strategic direction, investing and maintaining core competencies, promoting an effective organizational culture, emphasizing ethical practices, and setting balanced organizational controls, according to the model (Hitt et al, 2011). The study aims to understand the role of these dimensions in promoting strategic practices for human resource management, which includes several dimensions such as: Selection and Recruitment, Training and Development, Compensation, and Performance Evaluation. This was done based on the opinions of a number of researchers. The study was applied to a sample of 60 employees working in volleyball associations. To collect the data needed for the study, a questionnaire form was used. The study also used a set of statistical methods to analyze the results, including simple correlation coefficient and simple regression analysis using SPSS V.25 software. The study reached important results, most notably that employees attach great importance to employing people with competence and experience, in addition to providing them with different types of support and support in performing their tasks. The study concluded with a number of recommendations, the most important of which is the need to strengthen the awareness of volleyball federations of employees of the importance of strategic direction, in order to define a clear future vision and formulate Objectives and strategies and their effective implementation.